Utilization of Altimetry Satellite Data in Investigating the Energy Potential of Tidal Current - Junianto, Sony; Purnamasari, Ika; Habibi, Muhammad Nizar; Daffa, Muhamamd Zulfiqar; Yudiprasetyo, Nehemia Bagas (ROTASI, 2024)
Indonesia has a theoretical potential of tidal currents energy of 287 GW. The area that has the high potential is in the strait area. The tidal current has kinetic energy that can be converted into electricity using a Tidal Currents Energy Conversion System (TCECS). One of the potential straits is the Molo Strait. To determine the characteristics of tidal currents in the Molo Strait, local numerical modeling was carried out using tidal data and verified using publicly available field data. The equation used in local numerical modeling is the equation derived from the 3-dimensional Navier-Stokes equation by looking at the horizontal coordinates. The results of this modeling may be used to determine the power density and the type of turbine technology that is suitable to be applied in the Molo Strait. This paper reports that the Molo Strait has different two-way currents flow at high and low tides. In addition, the maximum mechanical power density at the potential point, coordinates (-8.625242°,119.805644°), in the spring and neap tides of the Molo Strait are 5.47 kW/m2, 5.18 kW/m2, 0.59 kW/m2 and 0.7 kW/m2, respectively. These may be calculated into mechanical power after determining the type and dimensions of the turbine technology.